Pancreatic Lipase Inhibitory Activity of Saraca Asoca bark Extract - Tiwari, Sweety; Gour, Rajesh; Kumar Singhai, Akhlesh (Journal of Neonatal Surgery, 2025)
Inhibition of pancreatic lipase is the mechanism that has received the greatest attention from researchers in the search for promising viable anti-obesity ingredients. For the purpose of locating possible anti-obesity drugs, the mechanism that has received the greatest attention from researchers is the inhibition of pancreatic lipase. Orlistat is the only medicine that has been licensed by the Food and Drug Administration (FDA) and is accessible for the treatment of obesity. Other than treatments that reduce obesity by acting on the central nervous system, orlistat is the only drug that inhibits pancreatic lipase. This naturally occurring chemical, known as lipstatin, was the starting point for the discovery of orlistat. The research that is being done to find novel pancreatic lipase inhibitors that do not have any negative side effects has been inspired by the effectiveness of naturally occurring substances that are used for the treatment of obesity. From this point forward, a great number of plant extracts and isolated substances have been found for their ability to inhibit pancreatic lipase. The stem bark of the Asoka tree is astringent, and it also functions as a uterine tonic and has a stimulating impact on the tissue of the ovary and the endometrium. Burning sensations, fever, and dyspepsia are among conditions that may be helped by the bark. This research was conducted to evaluate the methanol and aqueous extracts of Saraca asoca bark for pancreatic lipase inhibition activity.